2015
DOI: 10.9738/intsurg-d-15-00074.1
|View full text |Cite
|
Sign up to set email alerts
|

Stump Invagination Versus Simple Ligation in Open Appendicectomy: A Systematic Review and Meta-Analysis

Abstract: The aim of this meta-analysis was to compare the superiority of stump closure between stump invagination (SI) and simple ligation (SL) during open appendicectomy (OA). The literature searching was conducted in MEDLINE, EMBASE, the Cochrane Library, and http://scholar.google.com. Available data was extracted by 3 independent reviewers. The clinical outcomes were analyzed by meta-analytic software to compare the difference between 2 methods during OA. The pooled odds ratios (ORs) and weighted mean differences (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Eleven RCTs (2634 patients) were included in the systematic review and meta-analysis by Qian et al Postoperative pyrexia and infections were similar between simple ligation and stump inversion groups, respectively, but the former group had a shorter operative time, less incidence of postoperative ileus, and quicker postoperative recovery. The clinical results revealed that simple ligation was significantly superior to stump inversion [173].…”
Section: Q47: Does Aspiration Alone Confer Clinical Advantages Overmentioning
confidence: 97%
“…Eleven RCTs (2634 patients) were included in the systematic review and meta-analysis by Qian et al Postoperative pyrexia and infections were similar between simple ligation and stump inversion groups, respectively, but the former group had a shorter operative time, less incidence of postoperative ileus, and quicker postoperative recovery. The clinical results revealed that simple ligation was significantly superior to stump inversion [173].…”
Section: Q47: Does Aspiration Alone Confer Clinical Advantages Overmentioning
confidence: 97%
“…A meta-analysis by Antoniou S.A. et al (2017) involving more than 5000 patients showed that the use of suture material, that is, appendix ligation is superior to other methods given the combined parameters of infection of the organ and the surface of the operating field [8]. In another study, Qian D. et al (2015) compared simple ligation and stump invagination, and no significant difference was found, and as a consequence, clinical results showed that simple ligation was significantly superior to stump invagination [24]. Abdominal drainage is also debated.…”
Section: Resultsmentioning
confidence: 99%
“…In a meta-analysis comparing closure and burial of the AS in OA, the rates of postoperative fever and wound infection were found to be similar between OA, and LA. When compared as for operative time, postoperative ileus and recovery rate, and closure of the AS, LA was found to be a relatively superior technique (18) .…”
Section: Discussionmentioning
confidence: 96%
“…Some studies suggest that postoperative ileus and length of hospital stay may adversely affect out- comes. However, the scientific quality of these studies is not adequate to effectively stop surgeons from burying the AS (18,19) .…”
Section: Discussionmentioning
confidence: 99%